2021
DOI: 10.1002/app.51940
|View full text |Cite
|
Sign up to set email alerts
|

Improving the flame retardancy of intumescent flame retardant/high‐density polyethylene composites using surfactant‐modified montmorillonite clay

Abstract: The use of layered nanomaterials in combination with intumescent flame retardant (IFR) provides an excellent means of preparing high‐performance flame retardant composites. In this study, montmorillonite (MMT) was modified with two different surfactants, namely dodecyl trimethyl ammonium bromide (DTAB) and tetraphenyl phosphonium bromide (TPB), and then combined with IFR to prepare high‐density polyethylene (HDPE) composites. The effects of modified MMT (P‐MMT and A‐MMT) on the thermal and flame retardant prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…In scientific research, montmorillonite (MMT) and halloysite, came from smectite and kaolinite respectively, were consistently reported as raw materials of FRs over the two decades. [50][51][52][53] Their unique layered or tubular nanostructure endows polymer matrices with enhanced thermal and/or mechanical properties, in addition to excellent suppression on heat release. Recently, sepiolite and vermiculite were also used to create fire-retardant coatings.…”
Section:  Starting Materialsmentioning
confidence: 99%
“…In scientific research, montmorillonite (MMT) and halloysite, came from smectite and kaolinite respectively, were consistently reported as raw materials of FRs over the two decades. [50][51][52][53] Their unique layered or tubular nanostructure endows polymer matrices with enhanced thermal and/or mechanical properties, in addition to excellent suppression on heat release. Recently, sepiolite and vermiculite were also used to create fire-retardant coatings.…”
Section:  Starting Materialsmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28] Moreover, different fillers like clay, zirconium-based compounds, zinc borate, zeolite, and kaolin were used in the production of polyethylene composite materials with/without intumescent flame retardant systems. [29][30][31][32][33][34] It was determined that there were two reasons for using the fillers. The first one was to reduce the production costs of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the efficiency of intumescent flame retardant, a series of strategies have been reported, such as microencapsulation to improve its water resistance [ 12 ], novel char-forming agents [ 13 ], and synergistic agents as additives [ 10 , 14 , 15 , 16 ]. It has been proven that synergistic agents (such as nanocaly [ 17 ], zeolites [ 18 ], metal–organic frameworks [ 19 ], graphene [ 20 ], zinc borate, and fume silica [ 21 , 22 ]) can effectively improve flame retardancy of polypropylene composites at a relatively low dosage (commonly less than 3 wt.%). Bayramli et al, reported that boron compounds show a maximum flame retardancy effect at 3 wt.% loading and the zinc borate-containing PP composites show the highest rating (V0) using the UL-94 test [ 23 ].…”
Section: Introductionmentioning
confidence: 99%